2017
DOI: 10.1515/znc-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activities of leaf and fruit essential oils from Eucalyptus camaldulensis

Abstract: The chemical composition of the essential oils from the leaves and fruit of Eucalyptus camaldulensis grown in Mersin, Turkey was analyzed using gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS) techniques. The biological activities (antibacterial and antifungal) were examined using the agar well diffusion method. The main leaf oil constituents were p-cymene (42.1%), eucalyptol (1,8-cineole) (14.1%), α-pinene (12.7%) and α-terpinol (10.7%). The main constituents of the fruit oil were euca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…14 1,8-Cineole (6.9%), pcymene (24.8%), cryptone (2.2%), and spathulenol (12.4%), with approximately equal amounts, were also identified in the present study but β-phellandrene had no trace. Terpenes pcymene (42.1%), 1,8-cineole (14.1%), α-pinene (12.7%), and α-terpineol (10.7%) had a high amount in the E. camaldulensis essential oil in the study of Dogan et al, 16 while α-pinene was found to be in very low percentage (1.5%) in the present study. In the study Maghsoodlou et al, 19 1,8-cineole (57.8%), globulol (3.1%), limonene (5.4%), and α-pinene (13.4%) were identified as main components of E. viminalis essential oil, while a minimal amount of limonene (0.8%) was identified in our study.…”
Section: Essential Oil Analysissupporting
confidence: 44%
See 1 more Smart Citation
“…14 1,8-Cineole (6.9%), pcymene (24.8%), cryptone (2.2%), and spathulenol (12.4%), with approximately equal amounts, were also identified in the present study but β-phellandrene had no trace. Terpenes pcymene (42.1%), 1,8-cineole (14.1%), α-pinene (12.7%), and α-terpineol (10.7%) had a high amount in the E. camaldulensis essential oil in the study of Dogan et al, 16 while α-pinene was found to be in very low percentage (1.5%) in the present study. In the study Maghsoodlou et al, 19 1,8-cineole (57.8%), globulol (3.1%), limonene (5.4%), and α-pinene (13.4%) were identified as main components of E. viminalis essential oil, while a minimal amount of limonene (0.8%) was identified in our study.…”
Section: Essential Oil Analysissupporting
confidence: 44%
“…14 The antifungal, antibacterial, antioxidant, and insecticidal properties of E. camaldulensis essential oil, which mainly contain terpenes such as pcymene, 1,8-cineole, β-phellandrene, and spathulenol, have been recorded. [15][16][17] The essential oil extracted from Eucalyptus viminalis Labill. (manna or ribbon gum), which is rich in terpene compounds such as 1,8-cineole, α-pinene, limonene, and aromadendrene, has also shown various biological effects such as antimicrobial, antioxidant, and insecticidal properties in recent years.…”
mentioning
confidence: 99%
“…Terpenoids (Figure 3) also have strong antibacterial effects [45][46][47][48][49] (Table 2). The monoterpenoids in terpenoids are mainly found in the genus Mentha, and previous studies have found that most of the compounds extracted from plants of the genus mentha have strong antimicrobial activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…In the present study, the phenyl propenes; estragole and isoeugenol, and the monoterpenes; eucalyptol, pulegone, terpineol, and thymol were chosen as models of essential oil components. These components exhibit considerable biological effects including antimicrobial, antifungal, antinociceptive, anti-inflammatory (Dogan et al 2017;Kfoury et al 2016;de Sousa et al 2011;Melo Júnior et al 2017;de Oliveira et al 2012;Wattanasatcha, Rengpipat, and Wanichwecharungruang 2012;Riella et al 2012) antioxidant (Kfoury et al 2014), and anesthetic (Reiner, Perillo, and García 2013) activities.…”
Section: Introductionmentioning
confidence: 99%